WASTE ANALYSIS IN OUTPATIENT SERVICES AT RS NAILI DBS USING LEAN PRINCIPLES - Rezeki, Aisyah Putri; Herri; Putra, Abdi Setia; Astiena, Adilla Kasni; Yetti, Husna; Kasra, Kamal (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background : Quality improvement (QI) is a practice that hospitals use to improve efficiency, clinical outcomes, employee satisfaction, and patient safety. One of the QI practices is the implementation of lean principles. Lean is a set of methods intended to eliminate waste and increase process efficiency. Lean implementation can have a significant impact on operational efficiency and effectiveness. This research is aimed at analyzing services at the RS Naili DBS Outpatient Installation using lean principles. Method : Data collection was carried out through direct observation of the outpatient service process from arrival to receiving doctor consultation services. From the observations, visualization of the service process was carried out using big picture mapping and analysis of waiting time and waste was carried out using lean principles. Apart from that, in-depth interviews were conducted with selected informants, namely from within the hospital and patients as service recipients. Result : The results of the research showed that the outpatient waiting time from the time the patient contacted the registration officer until the doctor's service was completed was 1 hour 18 minutes 50 seconds. This time still exceeds the minimum service standard set by the government, namely 60 minutes. The results of observations regarding waste, found as many as 36 types of waste spread across the queuing process, registration, polyclinic waiting room and clinic room.